FAMILY BUSINESS: TRADITIONAL AND INNOVATIVE SOURCES OF FINANCING - Klimentina Poposka, Iskra Stancheva Gigov (Institute of Economics-Skopje, University “Ss. Cyril and Methodius” in Skopje, Republic of North Macedonia, 2018)
Family businesses represent a major part in economy, hence in order to acquire profit and accelerate growth, they need durable financing. Access to capital is not always an easy for such kind of businesses, hereafter financing can be very quiet difficult and challenging, particularly from the family businesses view, maintaining control over their company as a key success factor, which can make financing options even more limited. Optimal combination of traditional and innovative financial sources might trigger the family business to switch from traditional toward innovative sources of financing, heavily bearing in mind the influence of such financing toward limitation and reducing the control and ownership structure in family businesses. This paper aim to determine which are the most used sources of financing by family businesses, and if they prefer to use traditional or non-traditional way of financing. The results show that there are an increasing number of non-traditional sources of capital such as family offices and high net worth individuals which are increasingly favored source of family business finance.
Keywords: Family business, financing s ources, b anking l oans, 3F, high net worth individuals (HNWI).